Deglutition and Cough in Different Degrees of Parkinson Disease - Gasparim, Aretuza Zaupa; Jurkiewicz, Ari Leon; Marques, Jair Mendes; Santos, Rosane Sampaio; Marcelino, Paulo Cesar Otero; Herrero, Francisco, Junior (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Parkinson disease is one of the pathologies mostly affecting deglutition.Objective: To analyze the efficiency of both deglutition and cough reflex in cases of laryngeal penetration or tracheal aspiration with food, in different severity stages of Parkinson disease. Study's way: contemporaneous cohort with transverse incision.Method: The sample had 38 patients in the study group and 38 individuals in the control group submitted to a neurologic evaluation and an otorhinolaryngological evaluation by transnasal fiberoptic laryngoscopy.Results: The cough reflex was manifested in 100% of patients without food offering. Alimentary stasis in piriform recesses and epiglottic vallecula in solid, pasty and liquid consistency was significant (p= 0.0000). The laryngeal penetration in liquid consistency was significant (p= 0.0036). Tracheal aspiration occurred in 06 patients of the study group in liquid consistency and it was absent in control group.Conclusion: The efficiency of deglutition in the study group prevailed in the solid consistency, followed by pasty and liquid consistencies. In the control group, deglutition was effective in all individuals. Cough reflex was efficient in most patients of the study group and prevalently inefficient in the subgroup 2.
Keywords: Parkinson disease; cough; deglutition disorders